Advanced Actuator Materials Powered by Biomimetic Helical Fiber Topologies. Issue 18 (3rd December 2019) - Spinks, Geoffrey M.
Abstract: Helical constructs are ubiquitous in nature at all size domains, from molecular to macroscopic. The helical topology confers unique mechanical functions that activate certain phenomena, such as twining vines and vital cellular functions like the folding and packing of DNA into chromosomes. The understanding of active mechanical processes in plants, certain musculature in animals, and some biochemical processes in cells provides insight into the versatility of the helix. Most of these natural systems consist of helically oriented filaments embedded in a compliant matrix. In some cases, the matrix can change volume and in others the filaments can contract and the matrix is passive. In both cases, the helically arranged fibers determine the overall shape change with a great variety of responses involving length contraction/elongation, twisting, bending, and coiling. Synthetic actuator materials and systems that employ helical topologies have been described recently and demonstrate many fascinating and complex shape changes. However, significant new opportunities exist to mimic some of the most remarkable actions in nature, including the Vorticella's coiling stalk and DNA's supercoils, in the quest for superior artificial muscles. Abstract : Mechanical actuation systems in plants and animals almost always involve helical structures and studies show that a helical arrangement of fibers in a compliant matrix generates a great diversity of movements and mechanical amplifications. Opportunities are identified to develop advanced artificial muscles since only a limited number of nature's mechanisms have been recreated in biomimetic systems to date.